Negative Effects of Mass Media and the Dominance of Foreign Culture in the City of Lahore, Pakistan - Bhatti, Muhammad; Gondal, Muhammad; Sheikh, Muhammad; Hammad, Ahmad; Zafar, Fareeha (American Scientific Research Journal for Engineering, Technology, and Sciences, 2016)
Lahore is heavily populated city of Pakistan and well known of its gardens and colleges. With the advancement in technology and enhancement in media activities, a study is conducted to find out the negative effects of mass media and dominance of foreign culture in the city of Lahore. To find out the reasons a small questionnaire with some interconnected questions is being used, respondent’s ages lie between eighteen to twenty four years. By the descriptive analysis and averages method the results were very clear, the youth has an urge of adopting new fashions and trends, which has made very easy for the dominating media monopolies to obsess the minds and make them to follow the media policies.